High-pressure salt templating strategy toward intact isochoric hierarchically porous carbon monoliths from ionic liquids. Issue 81 (2nd November 2017) - Zhang, Zhen; Feng, Junzong; Jiang, Yonggang; Feng, Jian
Abstract : Using a high-pressure salt templating approach, a crack-free, hierarchically porous carbon monolith with good monolithic formability and integrity was prepared from an ionic liquid. Abstract : Through a facile and novel high-pressure salt templating approach, a crack-free hierarchically porous carbon monolith without visible volume changes was prepared using 1-ethyl-3-methyl-imidazolium dicyanamide (Emim-dca) as a carbon precursor. TG-DSC and FT-IR measurements revealed that Emim-dca pyrolysis, decomposition, crosslinking and carbonization reactions occurred in turn at temperatures of 234–350 °C, 350–520 °C and 520–1000 °C, respectively, which provides a guide for the preparation of an intact porous carbon monolith. The porous carbon monolith prepared at 4 MPa is amorphous and composed of small, uniform carbon particles with interconnected interstitial pores. Its bulk density is 0.072 g cm −3 . Besides the advantages of well monolithic formability and integrity derived from high pressure strategy, interestingly, the obtained porous carbon monolith possesses a higher specific surface area compared to the porous carbon powders fabricated through ambient pressure salt templating. The meso and macro specific surface area of the resultant porous carbon monolith is nearly three times higher (314.0 versus 106.7 m 2 g −1 ) with the content of 4 nm mesopore increasing dramatically compared to that of porous carbon powders prepared under ambient pressure, while the architecture of micropores keeps unchanged. These results might be explained as follows. The high pressure compresses gas molecules from the decomposition reaction into the carbon skeleton to form super-mesopores and macropores and simultaneously disperses salt clusters, generating small (∼4 nm) mesopores. As a solution to volume expansion in powders obtained via salt templating, the high pressure results in a porous carbon with an intact monolithic shape without volume expansion or shrinkage. Thus, fiber-reinforced porous carbon composites can be prepared for ultra-high-temperature insulation using the high-pressure salt templating method.